2014
DOI: 10.1002/2014gl060711
|View full text |Cite
|
Sign up to set email alerts
|

A physical mechanism of the precipitation dipole in the western United States based on PDO‐storm track relationship

Abstract: It is known that the western United States (US) precipitation displays a north-south contrast, i.e., the so-called "precipitation dipole," during El Niño and La Niña winters. Furthermore, the Pacific Decadal Oscillation (PDO) has been known to modulate this precipitation dipole. However, the underlying physical mechanism regulating this modulation is not well understood. This study revisits previous studies and suggests a physical mechanism of precipitation dipole modulation based on the PDO-storm track relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 42 publications
8
25
0
Order By: Relevance
“…Although not without criticisms, self-calibrated Palmer Drought Severity Index (PDSIsc) has been widely used for such purposes (Dai, 2011;Vicente-Serrano et al, 2011;Wells et al, 2004). Sung et al (2014) further revealed that both the jet stream and storm track tend to move northward (southward) over the North Pacific during negative (positive) Pacific Decadal Oscillation (PDO) winters, contributing to the increase of precipitation over the northwestern (southwestern) United States, respectively. In addition, they found that the most severe PDSIsc anomalies were centered in Southern California (SoCal), whereas the drought in Northern California (NorCal) was less severe.…”
Section: Introductionmentioning
confidence: 99%
“…Although not without criticisms, self-calibrated Palmer Drought Severity Index (PDSIsc) has been widely used for such purposes (Dai, 2011;Vicente-Serrano et al, 2011;Wells et al, 2004). Sung et al (2014) further revealed that both the jet stream and storm track tend to move northward (southward) over the North Pacific during negative (positive) Pacific Decadal Oscillation (PDO) winters, contributing to the increase of precipitation over the northwestern (southwestern) United States, respectively. In addition, they found that the most severe PDSIsc anomalies were centered in Southern California (SoCal), whereas the drought in Northern California (NorCal) was less severe.…”
Section: Introductionmentioning
confidence: 99%
“…Drought in the SW has also been linked to large‐scale climate variability such as the El Niño–Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO) [e.g., Dettinger et al , ; Brown and Comrie , ; McCabe et al , ; Weiss et al , ; Dai , ; Wang and Kumar , ; Barnston and Lyon , ]. In addition, the PDO has been associated with storm track intensity in the North Pacific [ Weiss et al , ; S.S. Lee et al , ; Dai , ; Sung et al , ], a region known to influence weather patterns and drought conditions in the SW [ Prein et al , ]. Temperature has increased in the region [ Munson et al , ; Wang et al , ], as has the length of the growing season (~10–15 days since the mid‐1980s) [ Hoerling et al , ], along with an earlier shift in spring blooms [ Ault et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the PDO has been associated with storm track intensity in the North Pacific [Weiss et al, 2009;S.S. Lee et al, 2012;Dai, 2013;Sung et al, 2014], a region known to influence weather patterns and drought conditions in the SW [Prein et al, 2016]. Temperature has increased in the region [Munson et al, 2011;Wang et al, 2011], as has the length of the growing season (~10-15 days since the mid-1980s) [Hoerling et al, 2013], along with an earlier shift in spring blooms .…”
mentioning
confidence: 99%
“…Previous studies [e.g., Brayshaw et al ., , Nakamura et al ., , Sung et al ., ] showed that the large‐scale atmospheric response is sensitive to the position of the SST gradient. In particular, Brayshaw et al .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [e.g., Brayshaw et al, 2008, Nakamura et al, 2004, Sung et al, 2014 showed that the large-scale atmospheric response is sensitive to the position of the SST gradient. In particular, Brayshaw et al [2008] performed the sensitivity experiment of Hadley cell and jet to the change in location and intensity of SST meridional gradient using the aqua-planet model.…”
Section: 1002/2014gl062175mentioning
confidence: 99%